A break with charity a story about the Salem witch trials - Rinaldi, Ann (Scholastic, 1992)
While waiting for a church meeting in 1706, Susanna English, daughter of a wealthy Salem merchant, recalls the malice, fear, and accusations of witchcraft that tore her village apart in 1692.